Interdisciplinary model of patient care for groups at risk for malignant tumors of the skin - M. A. Ufimtseva; A. S. Shubina; V. V. Petkau; N. L. Struin; D. E. Emel'janov; E. A. Levchenko (Бюллетень сибирской медицины, 2019)
Introduction. Malignant skin tumors (MST) are an important interdisciplinary problem. Neoplasia data refer to tumors of apparent localization, therefore, they are found in the clinical practice of doctors of different profiles. The duration of the diagnostic period, as well as the prognosis, depends on the coordinated work of specialists.Aim. Development, implementation and evaluation of the effectiveness of an interdisciplinary model for managing patients at risk for malignant skin tumors.Materials and methods. A descriptive study included a study of the proportion of people at risk for developing MST, the nosological structure of the revealed MST among patients referred to the dermatological oncology room of the Sverdlovsk Regional Dermatovenerologic Dispensary for the period from 01.01.2016 to 31.12.2017 (total 3,275 patients), as well as 208 patients examined in the Sverdlovsk Regional Oncology Dispensary (SROD). The data of the “ONKOR” regional oncological information system were used.Results. An interdisciplinary model of managing patients at risk has been developed, including patient routing andtraining of specialists in various fields. As a result of the implementation of the model, 208 patients were examined, 208 of whom were diagnosed with skin cancer, 123 of whom had skin cancer, 11 cases of melanoma, Kaposi’s sarcoma in 2 cases, skin lymphomas in 4 patients, lymphosarcoma in 1 patient, amounted to 67.8% of the diagnoses of MST confirmed in the Sverdlovsk Regional Dermatovenerologic Dispensary of the Sverdlovsk Regional Oncology Dispensary. 9.6% of patients had dysplastic nevi, confirmed histologically. 1987 patients at risk of developing MST were taken under the dispensary observation by a dermatologist and venereologist.Conclusion. Тhe introduction of the algorithm of interdisciplinary interaction contributes to the improvement of the quality and accessibility of medical care to the population, the identification of patients at risk for the occurrence of MST, reducing the burden of non-core patients on oncology services.